Integração do sistema de controle interno: análise no âmbito do Governo Estado do Ceará - Reis, Francisco Cláudio Ferreira (2018)
Ceará’s Public Administration Control, in the field of internal control, is a responsibility of the Internal Control System of each Power, which integration, among other purposes, aims at enabling social control and support external control (Federal Constitution/88). The effective social control fosters and assists the control action in the State Public Administration, especially, the external control. This research had as general objective to evaluate the integration of the Internal Control System of the Powers in Ceará. The research is characterized as descriptive, with a qualitative approach, whose method has allowed, from the documentary analysis, to know the structure of the internal control parts in Ceará, as well as to analyze if these organs are functioning in an integrated way. As for the technical means or procedures, a bibliographical, documentary and, in addition, semi-structured interview with the representatives of the six organs of the State Internal Control System was used. The results of the research reveal that the internal control of the Powers has not yet been properly implemented; that the recent changes promoted in the Constitution of the State of Ceará of 1989 added to the internal control the challenge of adding the activities of ombudsman; that the concepts of internal control and internal control system are not yet consolidated, consequently the integration of this system, under the terms of the legislation, has not been implemented either; and that there is a power polarized interaction at the national level. On the other hand, they reveal that there is a concern on the part of the central organs of internal control of the powers with the integration of the ICS in the State level.